ANALISIS KESANTUNAN BERBAHASA ANAK PADA BUKU CERITA BERGAMBAR DI TAMAN KANAK-KANAK - Zalmi, Refila Yuni; Mahyuddin, Nenny (Jurnal Golden Age, 2021)
AbstractThe purpose of this research or research is to know the analysis of children's language politeness in story books that have pictures in Kindergarten. The methodology used in this research is a literature study. The data collection technique he carried out in this research was by examining, reviewing, and also concluding various relevant data sources he obtained from documents, articles, journals, and others, both secondary and primary sources using data analysis techniques. form of content analysis. Based on various research results, it shows that children's language politeness can be developed by using story books that have pictures in them. Story books that have pictures in them can be used as a medium of learning in familiarizing children with polite language according to the choice of reading content that will be presented to children. The results show that it is very important to develop children's language politeness from an early age, through habituation that is consistently trained, through picture story books children can be interested in seeing the images presented which will gain knowledge, new vocabulary and can also develop children's development.Keywords: language politeness, picture story books, children ABSTRAKTujuan dari pada riset ataupun penelitian ini ialah guna diketahuinya analisis kesantunan berbahasa anak pada buku cerita yang memiliki gambar pada Taman Kanak-kanak. Metodologi yang dipergunakan pada riset ini ialah studi literature. Teknik pengumpulannya data yang dilakukannya pada riset inu yakni dengan cara menelaah, mengkaji, serta juga menyimpulkan bermacam sumber-sumber data yang relevan yang diperolehnya dari dokumen, artikel, jurnal, serta lain-lain, baik itu sumber sekunder ataupun primer yang mempergunakan teknik analisa data berwujud analisa isi. Didasarkannya dari berbagai hasil riset menunjukkan bahwasanya kesantunan berbahasa anak dapat dikembangkan dengan mempergunakan buku cerita yang memiliki gambar didalamnya. Buku cerita yang memiliki gambar didalamnya bisa dijadikan sebagai media pembelajaran dalam membiasakan anak berbahasa yang santun sesuai dengan pemiliah isi bacaan yang akan disajikan kepada anak. Hasil penelitian menunjukkan bahwa kesantunan berbahasa anak sangatlah penting dikembangkan semenjak usia dini, melalui pembiasaan yang dilatih secara konsisten, melalui buku cerita bergambar anak dapat tertarik melihat gambar yang disajikan yang akan mendapatkan pengetahuan, kosakata baru dan juga dapat mengembangkan perkembangan anak.Kata Kunci: kesantunan berbahasa, buku cerita bergambar, anak